Nutritional-requirements of Cryptococcus-laurentii in sugar-cane vinasse medium - Costa, ACM; CECCATOANTONINI, SR; Tauktornisielo, S. M. (Inst Tecnologia Parana, 1992)
The growth of the yeast Cryptococcus laurentii in complete broth for yeast and in liquid and semi-solid sugar cane vinasse media supplemented with several nitrogen and phosphorus sources was analysed in order to evaluate its potential utilization as biomass producer from vinasse. The trials were performed in a 1-liter fermentor, at 30-degrees-C, under magnetic agitation for 48 hours, and initial pH 5.0 for the liquid media. The parameters analysed were biomass, protein, and final pH. For the semi-solid media, agitated flasks under rotational agitation for 24 hours, at 30-degrees-C, and initial pH 5.0 were used. The results obtained showed that the yeast did not grow well in liquid sugar cane vinasse media, both supplemented or not, in comparison to the complete broth for yeast. The protein content was also lower in liquid sugar cane vinasse media. The medium pH did not alter markedly during the cultivation. The best results were obtained in semi-solid sugar cane vinasse media with supplementation, probably due to the known polysaccharide production by this species, which allows a better survival to solid substrates.
Keywords: CRYPTOCOCCUS-LAURENTII; VINASSE; NUTRITION